2017
DOI: 10.1111/pde.13359
|View full text |Cite
|
Sign up to set email alerts
|

Fatal disseminated Trichosporon asahii fungemia in a child with acute lymphoblastic leukemia and a morbilliform eruption

Abstract: Trichosporonosis is a rare, life-threatening, opportunistic fungal infection that affects immunocompromised individuals with neutropenia, particularly those with underlying hematologic malignancies. We present the case of a 10-year-old boy with acute lymphoblastic leukemia who developed a diffuse, morbilliform eruption in the setting of fever and pancytopenia. He was found to have Trichosporon asahii fungemia with widespread visceral dissemination, and his condition rapidly deteriorated despite treatment. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Histopathology classically reveals dermal fungal yeasts and hyphae on a background of mild‐to‐moderate, predominantly neutrophilic infiltrate. Perivascular or vasculitic involvement is also sometimes seen . Trichosporon shares morphologic characteristics with other common fungal pathogens but tends to present with a wider range of fungal elements at any one time (including hyphae, pseudohyphae, blastoconidia, and arthroconidia) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathology classically reveals dermal fungal yeasts and hyphae on a background of mild‐to‐moderate, predominantly neutrophilic infiltrate. Perivascular or vasculitic involvement is also sometimes seen . Trichosporon shares morphologic characteristics with other common fungal pathogens but tends to present with a wider range of fungal elements at any one time (including hyphae, pseudohyphae, blastoconidia, and arthroconidia) .…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous T. asahii infections vary in presentation but manifest most commonly as purpuric, papulonodular, or pustular lesions with or without centralized necrosis. 2,5,6,13,14 Histopathology classically reveals dermal fungal yeasts and hyphae on a background of mild-tomoderate, predominantly neutrophilic infiltrate. Perivascular or vasculitic involvement is also sometimes seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other risk factors leading to trichosporonosis are cytotoxic chemotherapy, consumption of systemic corticosteroid, indwelling central catheters, prosthetic valve surgery, organ transplantation, and peritoneal dialysis. 132,236 A recent systematic review reported that hematological diseases (38.9% of the cases), mainly acute leukemia, are the most frequent underlying diseases that provide a condition for invasive trichosporonosis (IT). Neutropenia was observed in 85% of patients with hematological diseases; this supports the fact that neutrophils are, as for aspergillosis and candidiasis, essential for the prevention of IT.…”
Section: Trichosporonosismentioning
confidence: 99%
“… 131 Nguyen (2018) Trichosporon asahii Disseminated Infection 10-year-old boy with ALL Micafungin, AMB and voriconazole No Culture Died It is important to consider trichosporonosis in the evaluation of a critically ill individual with neutropenia and a rash, because the initial cutaneous presentation may appear benign and delayed therapy results in death. 132 Abbreviations: AMB, amphotericin B; LAMB, liposomal Amphotericin B; ALL, acute lymphocytic leukemia; AML, acute myeloid leukemia; CLL, chronic lymphocytic leukemia; PCR, polymerase chain reaction; MALDI-TOF MS, matrix-assisted laser desorption/ionization mass spectrometry; MRI, magnetic resonance imaging; HSCT, hematopoietic stem cell transplant; BAL, bronchoalveolar lavage; CT, computed tomography; HE, histopathologic examination; CSF, cerebrospinal fluid; MIC, minimum inhibitory concentration. …”
Section: Aspergillosismentioning
confidence: 99%